MAGE-A4 pMHC-targeted CAR-T cells exploiting TCR machinery exhibit significantly improved in vivo function while retaining antigen specificity - Naoko Imai; Hiroshi Shiku; Yoshihiro Miyahara; Linan Wang; Takuma Kato; Hiroshi Fujiwara; Hiroshi Miwa; Meiou Liu; Yasushi Akahori; Kohei Negishi (Journal for ImmunoTherapy of Cancer)
Background The development of chimeric antigen receptor (CAR)-T cell therapies for solid tumors has attracted considerable attention, yet their clinical efficacy remains limited. Therefore, various efforts have been made to improve the efficacy of CAR-T cell therapy. As one promising strategy, incorporating the T-cell receptor (TCR) machinery into CAR structures has been reported to improve the efficacy of CAR-T cells in studies using conventional CARs targeting such as EGFR. However, in the case of peptide/major histocompatibility complex (pMHC)-targeted CARs, the advantages of exploiting TCR machinery have not been fully elucidated. We recently developed MAGE-A4-derived pMHC (MAGE-A4 pMHC)-targeted CAR-T cells (MA-CAR-T cells) using a highly specific human scFv antibody against MAGE-A4p230-239/HLA-A*02:01. We aimed to determine whether MAGE-A4 pMHC-targeted CAR-T cells using the TCR machinery (Hybrid MA-TCR-T cells) exhibit superior functionality without compromising antigen specificity.Methods We constructed a retroviral vector expressing Hybrid MA-TCR where MAGE-A4 pMHC-specific scFv are fused to human TCR constant chains.Results Hybrid MA-TCR-T cells demonstrated superior in vitro functions compared with MA-CAR-T cells, while maintaining strict antigen specificity. In addition, functional superiority of Hybrid MA-TCR-T cells to MA-CAR-T cells became more pronounced on repetitive antigen stimulation. In particular, Hybrid MA-TCR-T cells significantly inhibited tumor growth in an immunodeficient mouse model more effectively than MA-CAR-T cells. Ex vivo analyses indicated that their enhanced therapeutic efficacy might result from higher infiltration of functionally active, less differentiated Hybrid MA-TCR-T cells in tumor tissues.Conclusions These findings suggest that leveraging the TCR machinery is a promising strategy for enhancing pMHC-targeted CAR-T cell therapy for solid tumors, potentially leading to more effective treatments.